(untitled) (West African Journal on Sustainable Development, 2024)
This study examined public awareness and quality of products as predictors of customer loyalty among consumers in awka metropolis. A total number of two hundred Consumers in Awka metropolis, Anambra state served as participant for the study. The advertising effectiveness measure, quality of products scale (QPS) and customer loyalty scale (CLS), were used to generate data. Three hypotheses were utilized for the study. The first hypothesis stated that public awareness will significantly predict customer loyalty at (β=.238, p<.05). The second hypothesis stated that quality of products will significantly predict customer loyalty at (β=.390, p<.05. The third hypothesis stated Public awareness and quality of products will jointly predict with customer loyalty (F=22.49, Adjusted R2=.245, p<.001). All hypotheses were accepted. Multiple linear regression statistics was used to analyze the data collected. The results also showed that public awareness significantly predicted customer loyalty among consumers in Awka metropolis, quality of products significantly predicted customer loyalty among consumers in Awka metropolis and public awareness and quality of products jointly predicted with customer loyalty among consumers in Awka metropolis. Therefore, based on these results, it was recommended that effective marketing campaigns needs to be developed to increase public awareness about different products. Utilize various channels such as social media, television, radio, and billboards to reach a wider audience and educate them about the features and benefits of different products.